Development of Two-Tier Multiple-Choice Diagnostic Test Instrument Based on Science Literacy on Chemical Equilibrium Material - Oktaviani, Salsabil Zhafirah; Harjono (Universitas Negeri Semarang, 2025)
This study aims to develop a Two-Tier Multiple Choice (TTMC) diagnostic test instrument based on science literacy to assess students' science literacy skills on chemical equilibrium material. This research employed a Research and Development (R&D) design using the 4D model (Define, Design, Develop, Disseminate). The research subjects consisted of 59 students. The developed instrument was a TTMC diagnostic test comprising 25 items. The development process included three main stages: (1) determining the scope of chemical equilibrium material, (2) collecting information regarding the use of TTMC instruments, and (3) constructing and validating the TTMC diagnostic instrument. Data were analyzed using the Rasch model, which involved expert validation, item validation, reliability testing, difficulty level analysis, item discrimination testing, and students' science literacy profiling. The results indicated that the developed instrument is valid with an average expert validation score of 102 out of 128 and a Scale-Content Validity Index (S-CVI) of 1. The reliability coefficient for the instrument was 0.73 for the small-scale trial and 0.78 for the large-scale trial, indicating good consistency. Furthermore, the instrument demonstrated good discriminative ability by categorizing students into three ability groups. The science literacy profile analysis showed that students' science literacy was in the